Altitudinal variation and conservation priorities of vegetation along the Great Rift Valley escarpment, northern Ethiopia - Aynekulu, Ermias; Aerts, R.; Moonen, P.; Denich, M.; Gebrehiwot, K.; Vågen, Tor-Gunnar; Mekuria, Wolde; Boehmer, H.J. (Springer, 2012)
Understanding plant species distribution patterns along environmental gradients is fundamental to managing ecosystems, particularly when habitats are fragmented due to intensive human land-use pressure. To assist management of the remaining vegetation of the Eastern Afromontane Biodiversity Hotspot, plant species richness and diversity patterns were analyzed along the main elevation gradient (1,000-, 2,760 m) of the Great Rift Valley escarpment in northern Ethiopia, using 29 plots established at 100-m elevation intervals. A total of 129 vascular plant species belonging to 59 families was recorded. Species richness and diversity showed a hump-shaped relationship with elevation, peaking at mid-elevation (1,900-2,200 m). Beta diversity values indicated medium species turnover along the elevation gradient and were lowest at mid-elevation. Elevation strongly partitioned the plant communities (r = 0.98; P < 0.001). Four plant communities were identified along the elevation gradient: Juniperus procera-Clutia lanceolata community (2,400-2,760 m), Abutilon longicuspe-Calpurnia aurea community (1,900-2,300 m), Dracaena ombet-Acacia etbaica community (1,400-1,800 m), and Acacia mellifera-Dobera glabra community (1,000-1,300 m). To optimize conservation of species and plant communities, it is recommended that a conservation corridor be established along the elevation gradient that includes all four plant communities. This strategy in contrast to creating single isolated reserves in zones with high species richness is necessary for the habitat protection of species with narrow elevational ranges, in particular the globally endangered Nubian dragon tree (Dracaena ombet).